Hemiboea roseoalba S.B. Zhou, X. Hong & F. Wen (Gesneriaceae), a new species from Guangdong, China (Bangladesh Journal of Plant Taxonomy, 2013)
A new species of Hemiboea, H. roseoalba, from Guangdong, China, is described and illustrated. It is similar to H. gracilis and H. angustifolia in leaf and flower shape, but can be distinguished by leaf blade with serrulate from the middle to the apex, lateral veins 7-9 on each side of midrib; peduncle 2.5-3.0 cm long, glabrous; cymes 4-6-flowered; triangular calyx base connate for c. 0.3 cm; pink corolla 4.0-4.3 cm long and margin of lobes curled or retroflexed; staminodes 3; pistil 3.7-4.0 cm long; disc 2 mm high and truncate stigma slightly swollen.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17391Bangladesh J. Plant Taxon. 20(2): 171-177, 2013